Tuning amphiphilic properties of Ni/Carbon nanotubes functionalized catalysts and their effect as emulsion stabilizer for biomass-derived furfural upgrading. (15th September 2020) - Herrera, C.; Barrientos, L.; Rosenkranz, A.; Sepulveda, C.; García-Fierro, J.L.; Laguna-Bercero, M.A.; Escalona, N.
Graphical abstract: Highlights: Effective conversion of furfural has been realized under mild conditions. The solvent ratio plays a key role in the enhancing of activity. The selectivity can be tuned by the experimental conditions. Small and uniform emulsion droplets give to the system the highest stability. Abstract: Three amphiphilic carbon nanotube-supported Ni catalysts have been prepared and tested regarding their emulsifying properties for the hydrogenation of furfural. The solid catalysts and emulsions were systematically characterized by different high-resolution techniques. The catalytic hydrogenation of furfural was evaluated in a mixture of two immiscible solvents under mild conditions. The wettability of the catalysts was tuned by adjusting the severity of the acid treatments during the catalyst's synthesis. It was found that the catalysts wettability played a crucial role in enhancing the catalytic activity. The lowest furfural conversion observed over Ni/CNTox2 and Ni/CNTp were attributed to the missing possibility to form stable emulsion droplets due to their either extreme hydrophilic or hydrophobic character, respectively. In contrast, the highest catalytic activity verified for Ni/CNTox1 catalyst was traced back to an improved dispersion of the nickel nanoparticles as well as the possible formation of stable emulsion droplets due to its amphiphilic character. All catalysts were selective towards cyclopentanone. However, the highest yield of cyclopentanone was found over the Ni/CNTox1 catalyst, which migrated towards the organic phase after its formation. This result highlights the simultaneous reaction and separation of key reaction products in emulsion, which greatly simplifies the isolation stages of target products.